Why The UN And the World Failed to Control the Israel-Palestine War Conflict, And Is the Two-State Formula an Ultimate Solution? - Narayana, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
A lasting end to the Israeli-Palestinian conflict can only come through a two-State solution. one that starts with Palestinian freedom and leads to shared peace and security in the region, or one that continues denying this freedom and dooms the region to endless conflict. “Israel should no longer entertain the illusion that there is somehow a third path whereby it can choose continued occupation and colonialism and apartheid and somehow still achieve regional peace and security.” The ceasefire and a renewed vision of a two-State solution are critical for preventing the proliferation of extremism and extremist ideologies, urging to start preparing an international peace conference “to address all the puzzle pieces of a two-State solution in a comprehensive manner”.
Keywords: United Nations; World; Israel; Palestine; Jerusalem; Gaza Strip